1995
DOI: 10.1515/hfsg.1995.49.6.512
|View full text |Cite
|
Sign up to set email alerts
|

Thermal Degradation and Thermooxidation of O-Acetyl-(4-O-methyl-D-glucurono)-D-xylan and Related Derivatives

Abstract: Four polysaccharide samples related to (4-O-methyl-D-glucurono)-D-xylan were analyzed by thermogravimetry (TG) and differential scanning calorimetry (DSC) in nitrogen and oxygen environments. The calculated difference in the measured fG-residues run in different environments and obtained at temperatures close to 300 °C by a dynamic experiment indicate the action of oxygen on the formation of gaseous products. The rats constants and activation energies of the degradation process in both environments indicate th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

1998
1998
2015
2015

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 12 publications
0
9
0
Order By: Relevance
“…It is found that many of the OH-groups at C2 and C3 of the xylanpyranosyl units are substituted by O-acetyl groups and the acetyl content varies between 8% and 14% [40][41][42]. Thus, Oacetyl-4-O-methylglucuronoxylan is generally utilized to represent the xylan-based hemicellulose (mainly the xylan content) [27,[43][44][45][46]. The average degree of polymerization (DP) of the hemicellulose is estimated to be much less than that of cellulose, leading to its thermally unstable during pyrolytic process.…”
Section: Configuration Of Main Constituents In Biomassmentioning
confidence: 99%
See 4 more Smart Citations
“…It is found that many of the OH-groups at C2 and C3 of the xylanpyranosyl units are substituted by O-acetyl groups and the acetyl content varies between 8% and 14% [40][41][42]. Thus, Oacetyl-4-O-methylglucuronoxylan is generally utilized to represent the xylan-based hemicellulose (mainly the xylan content) [27,[43][44][45][46]. The average degree of polymerization (DP) of the hemicellulose is estimated to be much less than that of cellulose, leading to its thermally unstable during pyrolytic process.…”
Section: Configuration Of Main Constituents In Biomassmentioning
confidence: 99%
“…4, such as acetic acid, glycolaldehyde, furfural and 1:4-anhydroxylopyronose [31,43,45,56,91]. The tar fraction from α-D-xylose condensation gave a more complex mixture of volatile products containing large amounts of glycoladhehyde (3.1%) [43].…”
Section: Fast Pyrolysis Of Xylan-based Hemicellulosementioning
confidence: 99%
See 3 more Smart Citations